Quality of Work Life for Library and Information Science Professionals in University Libraries of Kerala: An Investigative Study - Naseer, A. (Journal of Information and Knowledge, 2020)
The study examines Quality of Work Life (QWL) of Library and Information Science (LIS) professionals. Respondents are two hundred and sixty-six LIS professionals working in the eight state universities in Kerala. The purpose of the study is to investigate and analyze QWL of LIS professionals in the universities. Data was collected through census method using a structured questionnaire. QWL of LIS professionals was measured using a modified QWL scale constructed based on Walton’s QWL dimensions. The study finds that the LIS professionals working in the universities of Kerala have different dimensions of QWL. The study found a significant difference in QWL in libraries of different universities. The study will be useful for enhancing QWL practices, improving organizational climate, job satisfaction and job motivation in library and information centres. QWL will enhance professional and personal life of employees and efficiency of organization.